Redes de memórias de uma mulher artista: em busca de 'um lugar ao sol'... - Lima, Maria Aparecida da Fonseca (2023)
This dissertation discusses an artistic journey, through autobiography, where the narrative of memories is made, problematizing the search for ‘a place in the sun’ as a woman, poet, writer, and painter. Based on the concept of ‘Creation Networks’ as a process of construction of works of art (SALLES, 2004; 2006), it is rescued the networks that carry out a process of creation, networks of an artist's path, bringing the intertwining of the path of this artist with others, namely: Nice Firmeza, Heloisa Juaçaba and her own mother. For this narrative - autobiographical and biographical -, in addition to memories, bibliographical and iconographic sources and documents such as newspapers, magazines, scientific articles, personal letters, among others, are used. The text is organized into two parts: in the first, the basic networks of the artist's path are highlighted; and, in the second, the threads of this artist's painting and literary works are rescued. This work also brought, as some of its results, the opportunity for the artist to get closer to the process itself (when perceiving her own creation network, completely unfinished) and with other networks of processes that were collectivized along the way.